Omphalitis in term and preterm appropriate for gestational age and small for gestational age infants - Güvenç, H; Aygün, AD; Yasar, F; Soylu, F; Güvenç, M; Kocabay, K (Oxford Univ Press, 1997)
To determine whether there is a difference on the historical and clinical characteristics of omphalitis among term and preterm appropriate for gestational age (AGA) and small for gestational age (SGA) infants, we prospectively investigated 85 newborns with bacteriologically proved omphalitis. Study groups were based on gestational age and being SGA, Preterm AGA infants had significantly lower mean age and neutrophil counts, Risk factors such as septic delivery including unplanned home delivery, and bacterial spectrum were similar in the groups, Staphylococcus aureus and Escherichia coli were the most frequent micro-organisms. Mortality rates for the study groups were similar and overall case fatality rate was 13 per cent. Immunological immaturity of preterm newborns may explain the earlier occurrence age of omphalitis and lower absolute neutrophil count. The following features such as early-onset infection, septic delivery including unplanned home delivery and abnormal temperature may be considered as determinants of poor prognosis. However, further studies are needed.
Keywords: Newborn-Infant